Smart building design conception, planning, realization, and operation - Bali, Maad (Birkhäuser, 2019)
How can smart technology open up new design opportunities for the design, the execution, and the operation of buildings and for the digitalization of construction? A hitherto unusual conception of the building as a cybernetic architectural system forms the basis of this integrated design approach. The authors--architects and engineers with extensive design experience--contribute an overview of current technical components of automation and communication systems, as well as a summary of relevant laws, standards, and guidelines. Six example projects demonstrate completed applications at different scales, from a single-family residence to office buildings, and through to the Elbphilharmonie concert hall, amply illustrated in text, drawings, and photos.